Verifying the outcomes of artesunate plus 595‐nm PDL in hypertrophic scars via determining BMP‐7 and Fas level in model rabbits. Issue 5 (1st March 2022) - Zhang, Jinxia; Luo, Wanting; Han, Minna; Wu, Lili; Peng, Zhuoying; Xia, Zhikuan; Yang, Rongya
Abstract: Background and Objectives: Single‐use of artesunate (ART) or 595‐nm pulsed‐dye laser (PDL) has proven clinical efficacy in the treatment of hypertrophic scars (HSs), yet little research has been done on the combined use of ART and PDL. Bone morphogenetic protein‐7 (BMP‐7) and Fas are recognized to be two important proteins in reducing scar formation. This study was designed to observe the effect of ART combined with 595‐nm PDL in the treatment of HS in rabbit models, and investigate the effect of such protocol on the expression of BMP‐7 and Fas in rabbit models. Study Design/Materials and Methods: Twenty‐four New Zealand white rabbits were randomly divided into the control group, ART group, PDL group, and combined treatment (ART + PDL) group. ART was respectively applied to the ART group and combined treatment group. Treatment was once every 2‐week for a total of three sessions for both groups. Animals in the PDL group were simply treated with 595‐nm PDL. Then, hematoxylin & eosin and Van Gieson straining, immunohistochemical study, enzyme‐linked immunosorbent assay (ELISA), Cell counting kit‐8 test, western blot assay, and real‐time polymerase chain reaction (RT‐PCR) were carried out to observe the development of HS samples and expression of BMP‐7 and Fas proteins in the sample tissues. Results: After treatment, the scar samples grew lower and flatter, which was particularly evident in the combined treatment group, with notably inhibited fibroblast and collagen compared to other groups ( p  < 0.001). Western blot assay and RT‐PCR demonstrated that the expression of BMP‐7 was most increased in scar samples treated by ART + PDL. BMP‐7 level was correspondingly and notably upregulated in treatment groups, especially in the ART + PDL group. In addition, relevant expression of Fas was also higher after treatment, especially in the ART + PDL group compared to either ART or 595‐nm PDL group. The difference was significant among groups ( p  < 0.001). Conclusions: Combined use of ART and 595‐nm PDL can inhibit HSs in rabbit models via inhibiting extra fibroblast and collagens. The potential mechanism may be involved in enhanced BMP‐7 and Fas expression. Our observations may create an alternative therapeutic strategy for HSs in the clinic.